Thermo-Dynamics of Plates and Shells - Awrejcewicz, Jan; Krys'ko, Vadim Anatolevich; Krys'ko, Anton V. (Foundations of Engineering Mechanics, 2007)
This monograph is devoted to the investigation of nonlinear dynamics of plates and shells embedded in a temperature field. Numerical approaches and rigorous mathematical proofs of solution existence in certain classes of differential equations with various dimensions are applied. Both closed shell-type constructions and sectorial shells are studied. The considered problems are approximated by 2D and 3D constructions taking into account various types of nonlinearities (geometrical and/or physical with coupled deformation and temperature fields), and are subjected to an action of stationary and non-stationary thermal loads. Variational and finite difference numerical approaches are used to study numerous problems important for civil and mechanical engineering. Furthermore, a novel and exact computational method to solve large systems of linear algebraic equations especially suitable for computational speed and memory storage of a computer is proposed. This book is expected to be useful for researchers, engineers and students dealing with thermal and dynamical problems of stability and strength of shell-type constructions.